Lectin domains at the frontiers of plant defense - Lannoo, Nausicaä; Van Damme, Els J. M. (Frontiers in Plant Science, 2014)
Plants are under constant attack from pathogens and herbivorous insects. To protect and defend themselves, plants evolved a multi-layered surveillance system, known as the innate immune system. Plants sense their encounters upon perception of conserved microbial structures and damage-associated patterns using cell-surface and intracellular immune receptors. Plant lectins and proteins with one or more lectin domains represent a major part of these receptors. The whole group of plant lectins comprises an elaborate collection of proteins capable of recognizing and interacting with specific carbohydrate structures, either originating from the invading organisms or from damaged plant cell wall structures. Due to the vast diversity in protein structures, carbohydrate recognition domains and glycan binding specificities, plant lectins constitute a very diverse protein superfamily. In the last decade, new types of nucleocytoplasmic plant lectins have been identified and characterized, in particular lectins expressed inside the nucleus and the cytoplasm of plant cells often as part of a specific plant response upon exposure to different stress factors or changing environmental conditions. In this review, we provide an overview on plant lectin motifs used in the constant battle against pathogens and predators during plant defenses.